Towards sustainable urban agriculture in the arid GCC states: Drivers of technology adoption among small-scale farmers - Elnazir Ramadan; Suliman Abdalla; Ali Al Ahbabi; Tarig Gibreel; Naeema Al Hosani (City and Environment Interactions, 2025)
In arid regions of the Global South, particularly the Gulf Cooperation Council (GCC) states, adopting agricultural technologies is vital for maximizing productivity and achieving sustainability. Despite their demonstrated benefits, adoption rates among small-scale farmers remain low due to water scarcity, environmental degradation, and socio-cultural and institutional barriers. This study explores the factors that influence farmers’ perceptions and decisions to adopt agricultural technologies, in small-scale urban farms in the pre-urban areas., providing valuable insights for enhancing adoption in these challenging environments. By utilizing the Unified Theory of Acceptance and Use of Technology (UTAUT) framework, along with diffusion of innovation, institutional and risk theories, data was gathered through a structured questionnaire and analyzed using ordinal logistic regression (OLR). The analysis identified key drivers of adoption, including performance expectancy, effort expectancy, social influence, facilitating conditions, trust in government and technology providers, and cultural norms. Perceived risk negatively influenced adoption, while compatibility was not statistically significant. The findings highlight the importance of creating supportive environments through transparent communication, infrastructure development, and tailored assistance. Recommendations focus on leveraging social networks, fostering trust, mitigating risks, and aligning technologies with cultural practices to scale up sustainable technology dissemination. This study offers valuable insights for policymakers and practitioners aiming to promote agricultural technology adoption in arid environments, contributing to sustainable development discourse in the Global South.